Associations between emotion regulation, feeding practices, and preschoolers’ food consumption - Santos, A. F. (2022)
: Previous research identified emotion dysregulation, non-responsive feeding practices, and unhealthy food consumption as risk factors for childhood obesity. However, little is known about the relationships between these factors. This study examined associations between children’s emotion regulation, parental feeding practices, and children’s food consumption. The sample consisted of 163 mothers of children aged 3–5 years. Mothers completed the Emotion Regulation Checklist, the Child Feeding Questionnaire, and the Child Health Section from the Parent Interview of the Early Childhood Longitudinal Study-B to assess model variables. Results showed that healthy food consumption was associated with higher emotion regulation abilities, higher monitoring, and lower pressure to eat. For unhealthy food consumption, the associations were in opposite directions. Higher emotion regulation abilities were also associated with higher monitoring, lower pressure to eat, and lower restriction. For lability, the associations were in opposite directions. Regression analyses revealed that children’s lability, pressure to eat, and monitoring were significant predictors of children’s food consumption. These findings suggest that children’s emotion regulation and feeding practices are important determinants of children’s food consumption. Future longitudinal studies that examine bidirectional associations between children’s emotion regulation, parental feeding practices, children’s food consumption, and potential mechanisms accounting for these associations are needed.